Produtividade e qualidade de beterraba em função da adubação nitrogenada e potássica - Nogueira, Henrique Campos (2020)
The objective of this work was to evaluate the productivity and quality of beet as a function of nitrogen and potassium fertilization. The work was carried out at the Rafael Fernandes Experimental Farm, belonging to the Federal Rural University of Semi-arid, located in the district of Alagoinha, in Mossoró-RN. The experimental design was randomized complete blocks in a 4 x 4 factorial scheme, with four replications. The treatments will consist of the combination of four doses of nitrogen (0; 40; 80 and 120 kg ha-1 of N) and four of potassium (0; 60; 120 and 180 kg ha-1 of K2O). The following characters were evaluated: Plant height; levels of N and K in the diagnostic sheet; commercial productivity; non-commercial productivity; total productivity; percentage of white rings inside the roots, soluble solids and total soluble sugars. Nitrogen contributed more significantly to root growth, productivity and quality, than potassium. Commercial productivity (12.2 tha-1) was maximized with application of 120 kg ha-1 of N. The use of the dose that maximized root productivity, without application of potassium, did not significantly reduce the quality of the root of beet